PERSISTENSI HERBISIDA METOLACHLOR DAN PENDIMETHALIN PADA TANAH BERBEDA KANDUNGAN BAHAN ORGANIK - Baidhawi Baidhawi (Universitas Padjadjaran, 2014)
AbstractThe experiment was conducted at glasshouse owned by Faculty of Agriculture Padjadjaran University, Bandung, Indonesia from June until August 2012. The objective of this experiment was to determine the persistence of metolachlor pendimethalin herbicide in four different soils (ultisol jatinangor I, II, III and compost) organic matter content using bioassay tecnhnique. The design experiment used was complete block design with factorial pattern. There were three factors. The first factor was dose of pendimethalin herbicide: 0.00, 0.75, 1.5, and 2.25 kg ai ha-1. The second factor was soil organic matter content: 1.9, 4.40, 5.98, 6.24, and 12.4 %. The third faktor was type of herbicide (metolachlor and pendimethalin). Cucumber was used as a test crop. The dry weights of cucumber were used as parameter to detect the residue of pendimethalin in soils. There was a interaction between the dose of pendimethalin and soil organic matter contents. The treatment combination of 0,75 a.i ha-1 and soil with 12,4% organic matter content showed the lowest persistence of pendimethalin in soil, whereas the highest persistence of pendimethalin was with the treatment combination of 2.25 a.i ha-1 and soil with 1.9% organic matter content.Keywords: Pendimethalin, organic matter, bioassay, cucumber, HPLC